Pengaruh Personalisasi Digital, Kepercayaan Terhadap Influencer, dan Keterlibatan Pelanggan Terhadap Keputusan Pembelian Online di Kalangan Gen Z - Abbas, Muchlis; Rahmawati Umar; Masyadi; Muin, Asri Nur (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study explores the influence of digital personalization, trust in influencers, and customer engagement on online purchase decisions among Generation Z. As digital technology continues to evolve, consumer behavior—especially among Gen Z—has shifted toward more personalized, interactive, and influencer-driven experiences. Gen Z, being digital natives, respond strongly to tailored content and value engaging, trustworthy digital interactions in their purchasing journey. Using a quantitative explanatory approach, data were collected through a structured survey targeting Gen Z individuals who are active social media users and frequent online shoppers. The results reveal that all three variables—digital personalization, trust in influencers, and customer engagement—have a positive and significant impact on online purchase decisions. Among these, customer engagement emerges as the most influential factor in shaping purchase behavior. These findings highlight the critical role of personalized digital experiences, credible influencer relationships, and meaningful brand-customer interactions in driving Gen Z’s online buying decisions.